Pengaruh Disiplin Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kementerian Kependudukan dan Pembangunan Keluarga Jakarta: The Influence of Work Discipline and Organizational Culture on Employee Performance at the Ministry of Population and Family Development in Jakarta - Siti Nur Aisyah Puspanegara; Susan Rachmawati (CV Warnak Johanna Nusantara, 2026)
The purpose of this study is to determine the effect of work discipline and organizational culture on the performance of employees in the Human Resources Bureau of the Ministry of Population and Family Development in Jakarta. The method used is quantitative statistics, with a total of 40 respondents using a saturated sample. Data was collected by distributing questionnaires and processed using SPSS software version 25. Hypothesis testing used multiple linear regression, through t-tests and f-tests, which aimed to determine the independent variables against the dependent variables. The results of the t-test showed that the work discipline variable had a positive and significant effect on employee performance, as seen from the t-value of 4.799 > 2.026 and a significance value of 0.000 < 0.05. while the organizational culture variable had a positive and significant effect on employee performance, as seen from the t-value of 2.115 > 2.026 with a significance value of 0.041 < 0.05. In testing the f variable, work discipline and organizational culture have a simultaneous or simultaneous effect on employee performance, as can be seen from the f count value of 21.145 > f table 3.245 with a significance value of 0.000 < 0.05